Finite element analysis of piston crown for a diesel engine / Arif Akmal Rozman - Rozman, Arif Akmal (2024)
The objectives of this project is to locate stress and heat concentration on piston crown of diesel engine using Finite Element Method and to analyse structural integrity of various material of piston crown for diesel engine. An existing diesel engine piston is measured to obtained dimensions which will be modelled in Solidwork. Then the model will be analysis using Finite Element Analysis in Ansys Workbench. The boundary conditions use engine speed at certain speed in rpm. The results will show the maximum value for each different piston material in three boundary conditions which is total deformation, equivalent stress and total heat flux. The conclusion of this analysis is to determine the best piston material to use in a diesel engine.